Manajemen Perencanaan Program Halaqah Lughawiyah Perspektif Kognitif Jean Piaget di Pondok Pesantren Al-Umm Malang - Maghfirotunnisa, Alfi; Mutiara Rizqy Amalia,; Naufal Fikri, (Shaut al Arabiyyah, 2023)
Pondok Pesantren is an educational institution with a distinctive scientific tradition. A good form of institutional planning will have a positive impact and can be tangible evidence in accordance with the established vision and mission. Management of program planning at Al-Umm Islamic Boarding School was initiated by caregivers and their staff to ground and maintain the existence of Arabic in the pesantren environment in the modern era. In the discussion, the researcher limits the problem to two formulations, first, to describe the scope of the Halaqah Lughowiyah program planning at Pondok Pesantren Al Umm Malang. Second, how is the process of planning the Halaqah Lughowiyah program at Pondok Pesantren Al Umm Malang based on Jean Piaget's cognitive theory. This research is included in descriptive qualitative research with data collection techniques using observation, interviews, and document analysis. Data analysis in this study uses Miles and Huberman analysis in the form of data reduction, data display, and conclusions. The results of the study stated that the management of Arabic language program planning at Pondok Pesantren Al Umm Malang: First, the Halaqah Lughawiyah Program is a program that uses the Interactive Approach model and is included in the Medium Term Planning dimension with a period of three years. Second, the achievement of this program planning relies on Jean Piaget's cognitive learning theory according to its implications in terms of its cognitive learning objectives and its developmental phase in the formal operational phase, namely the application of programs aged 12 years and over.